Dementia in Kerala, South India: prevalence and influence of age, education and gender - Mathuranath, P. S. (Int J Geriatr Psychiatry, 2010)
BACKGROUND: Data on the prevalence of dementia in India with a large and aging population is scant. We studied prevalence of AD and dementia in Kerala, South India, and effects of age, education and gender on it. METHODS: 2-phase survey on 2466 individuals aged ≥55 years living in community. Men constituted 41%, < 75 years age in 76.9% and education ≥4 years in 69.6%. Screening (Phase I) using the instrumental activity of daily living scale for the elderly (IADL-E) and the Addenbrooke’s cognition examination (ACE). Diagnostic-assessment (Phase II) was in 532 screen-positives and 247 (10%) screen-negatives. RESULTS: 93 (3.77%) ≥55 years and 81 (4.86%) ≥65 years of age had dementia. Age adjusted (against US-population in 2000) dementia (and AD) rates were 4.86% (1.91%) in age ≥55 years and 6.44% (3.56%) in ≥65 years. Odds for dementia (and AD) were high with increasing-age 5.89 (15.33) in 75–84, 13.23 (25.92) ≥85 years, and in women 1.62 (2.95); and low 0.27 (0.16) if education was ≥9 years. Age and low education increased dementia. Age and female gender increased AD. CONCLUSION: Prevalence of dementia and AD is higher than any reported from the subcontinent suggesting that dementia in Kerala in South India is not uncommon. Increasing age increased dementia and AD. Low-education is associated with dementia and female-gender with AD.